Socio-economic conditions, young men and violence in Cape Town - Seekings, Jeremy (2016)
People in violent neighbourhoods attribute violence in public spaces to, especially, poverty and unemployment, but agree that social disintegration, disrespect, drinking and drugs and the weaknesses of the criminal justice system also contribute substantially. However, data from a panel of young men in Cape Town provide little support for the hypothesis that unemployment and poverty are direct causes of violence against strangers. Growing up in a home where someone drank heavily or took drugs is, however, a strong predictor of violence against strangers in early adulthood. A history of drinking (or taking drugs) correlates with perpetration of violence, and might also serve as a mechanism through which conditions during childhood have indirect effects. Living in a bad neighbourhood and immediate poverty are associated with violence against strangers, but being unemployed is not. Overall, heavy drinking - whether by adults in the childhood home or by young men themselves - seems to be a more important predictor of violence than economic circumstances in childhood or the recent past. Heavy drinking seems to play an important part in explaining why some young men have been more violent than others in circumstances that seem to have been generally conducive to rising violence, for reasons that remain unclear. It seems likely that few young people in South Africa in the early 2000s come from backgrounds that strongly predispose them against the use of violence